Hair Dye Poisoning in a Paediatric Patient - Jolly Chandran; Rimi Manners; Indira Agarwal; Kala Ebenezer (Case Reports in Pediatrics)
Hair dye ingestion with suicidal intention has increased among rural Indian population and is associated with significant mortality. We report a teenager who presented with cervicofacial edema, respiratory distress, rhabdomyolysis, and myocarditis after ingesting the hair dye Super Vasmol 33. Early and supportive treatment can prevent morbidity and mortality.